The Ambiguous Roles of Extracellular Vesicles in HIV Replication and Pathogenesis - Dias, Marcos V. S.; Costa, Cristina S.; daSilva, Luis L. P. (Frontiers in Microbiology, 2018)
Cells from all kingdoms of life can release membrane-enclosed vesicles to the extracellular milieu. These extracellular vesicles (EVs) may function as mediators of intercellular communication, allowing the transfer of biologically active molecules between cells and organisms. It has become clear that HIV particles and certain types of EVs, such as exosomes, share many similarities regarding morphology, composition, and biogenesis. This review presents a summary of the literature describing the intricate relationship between HIV and EVs biogenesis. Also, we discuss the latest progress towards understanding the mechanisms by which EVs influence HIV pathogenesis, as well as, how HIV modulates EVs composition in infected cells to facilitate viral spread.